Analysis of organizational commitment in determining the success of Accounting Information Systems (AIS) in the banking sector - Ita Salsalina Lingga (The Indonesian Accounting Review, 2021)
This study aims to examine the effect of organizational commitment on the success of accounting information systems (AIS). The unit of analysis in this study was Regional Development Banks (Indonesian: Bank Pembangunan Daerah / BPD) throughout Indonesia. Data collected by using a questionnaire. The respondents were BPD employees as the AIS users. The total research sample used was 275, while the questionnaire return rate was 64% (176). The data were processed and analyzed using the Partial Least Square SEM method. The results proved that organizational commitment has no effect on the success of accounting information system. In general, BPD employees’ commitment to the organization is at the “adequate” level, which means that they are not fully committed to supporting the success of the accounting information system. The results of this study do not support the theory and results of previous studies which state that organizational commitment affects the success of the accounting information systems.